The Experiences of Nontraditional Students: A Qualitative Inquiry. Issue 3 (2nd September 2017) - Bohl, Amanda J.; Haak, Beatriz; Shrestha, Srijana
Abstract: The number of nontraditional students enrolled in higher education is rising, but retention of these students is a challenge. This study used a qualitative framework to examine the experiences of nontraditional undergraduate students in a university setting. Nine participants completed open-ended questionnaires, and we transcribed and coded the responses for themes. When discussing their experiences, participants spoke of five overarching themes: motivations to return, academic challenges, generation gap, support systems, and benefits of being a nontraditional student. This study contributes to the literature, providing insight to the overall collegiate experience of degree-seeking, nontraditional students.